Do hospital pressures change following rotavirus vaccine introduction? A retrospective database analysis in a large paediatric hospital in the UK. Issue 5 (15th May 2019) - Heinsbroek, Ellen; Hungerford, Daniel; Cooke, Richard P D; Chowdhury, Margaret; Cargill, James S; Bar-Zeev, Naor; French, Neil; Theodorou, Eleni; Standaert, Baudouin; Cunliffe, Nigel A
Abstract : Objective: Hospitals in the UK are under increasing clinical and financial pressures. Following introduction of childhood rotavirus vaccination in the UK in 2013, rotavirus gastroenteritis (RVGE) hospitalisations reduced significantly. We evaluated changes in 'hospital pressures' (demand on healthcare resources and staff) following rotavirus vaccine introduction in a paediatric setting in the UK. Design: Retrospective hospital database analysis between July 2007 and June 2015. Setting: A large paediatric hospital providing primary, secondary and tertiary care in Merseyside, UK. Participants: Hospital admissions aged <15 years. Outcomes were calculated for four different patient groups identified through diagnosis coding (International Classification of Disease, 10th edition) and/or laboratory confirmation: all admissions; any infection, acute gastroenteritis and RVGE. Methods: Hospital pressures were compared before and after rotavirus vaccine introduction: these included bed occupancy, hospital-acquired infection rate, unplanned readmission rate and outlier rate (medical patients admitted to surgical wards due to lack of medical beds). Interrupted time-series analysis was used to evaluate changes in bed occupancy. Results: There were 116 871 admissions during the study period. Lower bed occupancy in the rotavirus season in the postvaccination period was observed for RVGE (−89%, 95% CI 73% to 95%), acute gastroenteritis (−63%, 95% CI 39% to 78%) and any infection (−23%, 95% CI 15% to 31%). No significant overall reduction in bed occupancy was observed (−4%, 95% CI −1% to 9%). No changes were observed for the other outcomes. Conclusions: Rotavirus vaccine introduction was not associated with reduced hospital pressures. A reduction in RVGE hospitalisation without change in overall bed occupancy suggests that beds available were used for a different patient population, possibly reflecting a previously unmet need. Trials registration number: NCT03271593